Phase Noise Tracking: Circuit design and construction - Thunberg, Hugo; Olson, Johan (My University, 2022)
In order to detect small targets in an environment with interference using radar systems, an oscillator exhibiting low phase noise is required. An oscillator with poor phase noise can disguise the object of interest due to clutter. Therefore a method has been proposed to reduce phase noise, but in order for this method to be implemented, phase noise must first be measured. The goal of this thesis has been to design and construct a system capable of estimating the instantaneous phase noise of an oscillator. In addition, the system has been analyzed to determine its functionality, where its potential to measure low phase noise was vital. This thesis was limited to the delay line discriminator method, since all other methods rely on their own local oscillators. However, a variant using a RF-interferometer was investigated as well. Three different designs were constructed and all were analyzed ,using software before construction. The first served as a proof of concept while the second was intended as the final product. Although, a variant of it was proposed and constituted the third design, adding a RF-interferometer. All designs went through similar experiments were the phase noise from an oscillator had modelled phase noise superimposed on its own. The system output was measured using an analogto- digital converter. The data collected shows that all the systems could measure instantaneous phase noise correctly. However, while functional, the conventional delay line discriminator suffer limitations in measuring low phase noise, in particular low frequency offset phase noise, at its lowest −47 dBc/Hz at 100 Hz. Two reason for this limitation was identified. First, the delay line discriminator itself filters low frequency offset phase noise, while the second limitation was caused by noise generated from a component in the system, namely the frequency mixer. This limitation was mitigated by using the RF-interferometer variant, which has better sensitivity, in particular at these low frequencies (−71 dBc/Hz at 100 Hz) and for short time delays. Still, it can be concluded that if the phase noise is sufficiently large, all designs investigated performs well. Ultimately, it is up to future studies to conclude whether the delay line discriminator is sensitive and robust enough to use in radar systems, and if the proposed method yields a worthwhile reduction of phase noise.